2015
DOI: 10.1007/s10162-015-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Otopathology Following Systemic and Intracerebroventricular Delivery of 2-Hydroxypropyl-Beta-Cyclodextrin

Abstract: Cyclodextrins are simple yet powerful molecules widely used in medicinal formulations and industry for their ability to stabilize and solubilize guest compounds. However, recent evidence shows that 2-hydroxypropyl-β-cyclodextrin (HPβCD) causes severe hearing loss in mice, selectively killing outer hair cells (OHC) within 1 week of subcutaneous drug treatment. In the current study, the impact of HPβCD on auditory physiology and pathology was explored further as a function of time and route of administration. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
(32 reference statements)
8
33
3
Order By: Relevance
“…Ears with severe IHC and OHC damage had greater effects at the base than apex (Fig 7). While some of this variability in OHC loss may be attributable to the relatively short time-frame of our acute study, interanimal variability is nevertheless consistent with that reported from Crumling et al [5] and Cronin et al [6] who studied the chronic effects of HPβCD treatment. Treatment with MβCD consistently caused severe damage directly to the OHCs and IHCs or the regions around these sensory cells.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Ears with severe IHC and OHC damage had greater effects at the base than apex (Fig 7). While some of this variability in OHC loss may be attributable to the relatively short time-frame of our acute study, interanimal variability is nevertheless consistent with that reported from Crumling et al [5] and Cronin et al [6] who studied the chronic effects of HPβCD treatment. Treatment with MβCD consistently caused severe damage directly to the OHCs and IHCs or the regions around these sensory cells.…”
Section: Resultssupporting
confidence: 91%
“…But, a negative side effect of HPβCD-based treatments is hearing loss. Recent studies on the chronic effects of HPβCD administered systemically or directly into cerebrospinal fluid found graduated losses of outer hair cells (OHC) along the cochlear spiral, with more severe losses at the cochlear base than the apex [56]. While the origins of HPβCD toxicity within the ear remain uncertain, its effects can modulate cochlear or OHC electromechanics in excised cochleae [78].…”
Section: Introductionmentioning
confidence: 99%
“…In other two patients, despite delaying the next dose, hearing loss was not reversed. This AE was also observed in animal studies with IT [18], ICV [53], and intracisternal [25] routes of administration. At the dosage employed, hearing loss is an expected AE, as well as a well-known NPD-C symptom.…”
Section: Experience In Humans: Potential Toxicities Of the Different supporting
confidence: 56%
“…13,14) However, as described above CyDs occasionally show toxicity in the lung, 114) bone, 115) ears, 116) and kidney. 117) In contrast to the abundant safety data of CyDs, very few data are available on the safety of CyD-based supermolecules.…”
Section: Toxicology Of Cyclodextrin-based Supermoleculesmentioning
confidence: 82%
“…CyDs are also useful in inhibiting neuromuscular blockade by rocuronium (trade name: Bridion ® ) 111) and in increasing the immune responses of vaccines (adjuvant). 112,113) However, CyDs occasionally show toxicity in the lung, 114) bone, 115) ears, 116) and kidney. 117) Moreover, blood retention of CyDs is generally short, 13,117) resulting in low bioactivities.…”
Section: Cyclodextrin-based Supramolecular Pharmacology and Drug Discmentioning
confidence: 99%